Human N-Acetyltransferase 1 and 2 Differ in Affinity Towards Acetyl-Coenzyme A Cofactor and N-Hydroxy-Arylamine Carcinogens - Hein, David W.; Doll, Mark A.; Habil, Mariam R. (Frontiers in Pharmacology, 2022)
Arylamine N-acetyltransferases catalyze the transfer of acetyl groups from the endogenous cofactor acetyl coenzyme A (AcCoA) to arylamine (N-acetylation) and N-hydroxy-arylamine (O-acetylation) acceptors. Humans express two arylamine N-acetyltransferase isozymes (NAT1 and NAT2) which catalyze both N- and O-acetylation but differ in genetic regulation, substrate selectivity, and expression in human tissues. We investigated recombinant human NAT1 and NAT2 expressed in an Escherichia coli JM105 and Schizosaccharomyces pombe expression systems as well as in Chinese hamster ovary (CHO) cells to assess the relative affinity of AcCoA for human NAT1 and NAT2. NAT1 and NAT2 affinity for AcCoA was higher for recombinant human NAT1 than NAT2 when catalyzing N-acetylation of aromatic amine carcinogens 2-aminofluroene (AF), 4-aminobiphenyl (ABP), and β -naphthylamine (BNA) and the metabolic activation of N-hydroxy-2-aminofluorene (N-OH-AF) and N-hydroxy-4-aminobiphenyl (N-OH-ABP) via O-acetylation. These results suggest that AcCoA level may influence differential rates of arylamine carcinogen metabolism catalyzed by NAT1 and NAT2 in human tissues. Affinity was higher for NAT2 than for NAT1 using N-OH-AF and N-OH-ABP as substrate consistent with a larger active site for NAT2. In conclusion, following recombinant expression in bacteria, yeast, and CHO cells, we report significant differences in affinity between human NAT1 and NAT2 for its required co-factor AcCoA, as well as for N-hydroxy-arylamines activated via O-acetylation. The findings provide important information to understand the relative contribution of human NAT1 vs NAT2 towards N-acetylation and O-acetylation reactions in human hepatic and extrahepatic tissues.